Competence of Phortica variegata from the United States as an Intermediate Host of the Thelazia callipaeda Eyeworm - Otranto, Domenico (Am J Trop Med Hyg, 2018)
Over the past 20 years, Thelazia callipaeda (the oriental eyeworm) has become endemic in Europe, infecting domestic and wild carnivores and humans. The vector of this nematode, the fruit fly Phortica variegata, has recently been discovered in the United States, and its vector competence is demonstrated for T. callipaeda in this article, therefore representing a potential new threat for infection of carnivores and humans in the United States.